Alinhamento entre diretrizes para o desenvolvimento de competências do administrador e as competências demandadas pelo mercado de trabalho - Lima, Fernando Antônio Holanda (2023)
This study aims to analyze the alignment of skills in training, in the Administration course at the Federal University of Ceará (UFC), established in its Pedagogical Project of the Course (PPC, 2022), in compliance with Resolution Nº 5/2021 of the CNE, with the skills required by the market in Ceará. A qualitative, descriptive, documentary and field study was carried out, with six representatives of the Industries, Commerce and Services segments in the Ceará labor market. The results point to the fact that the alignment is present between the PPC of the course and the CNE/CES Resolution, as well as between the competences described in these documents and the competences required in the labor market. However, how to develop skills, tools and methods to be applied in the classroom was not presented in any of the documents, leaving it to the discretion of each teacher, not demonstrating how the expected results will be monitored or measured. Another factor observed is the difficulty in reducing existing distances between theory and practice with regard to the development of skills.